Characterisation of the cold metal transfer (CMT) process and its application for low dilution cladding - Pickin, Craig Graeme; Williams, Stewart W.; Lunt, M. (Elsevier Science B.V., Amsterdam., 2011)
The process characteristics of the synergic cold metal transfer (CMT) process have been examined for welding aluminium alloy. Utilising a simple backlighting system and through the arc monitoring the droplet transfer modes were identified. Whilst the modified short circuit mode was evident for the lower parameter range, a two part transfer mode based upon a combination of spray and short circuit transfer was observed for the mid to upper parameter range. The technology was also explored as a cladding process for applying to ternary alloyed (Al–Cu–Mg) aluminium plate. This alloy system is known to be susceptible to solidification cracking when MIG welded using the binary Al-2319 (Al–Cu) filler wire, this being due to the wide element freezing range of the weld resulting from mixing with the base material. Utilising this filler, weld dilution ratios for both CMT and pulsed welding were identified across the examined parameter range. The CMT process exhibited greater control of dilution that enabled deposition of a quasi-binary (Al–Cu) layer exhibiting a less crack susceptible composition. Onto this layer conventional MIG welding could be applied which could potentially eradicate cracking using a binary fil
Keywords: CMT; Welding; High strength aluminium; Arc characteristics